Implementation of the Bahtsul Masa'il Method in Improving Ability to Read the Book of Fathul Qorib - Hudri, Salman; Al Haj Zaini , Zainuddin; Mukaffan (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This research aims to investigate the effectiveness of implementing the Bahtsul Masa'il Method in improving the ability to read the Book of Fathul Qorib using a quantitative approach. This method is used in the context of Islamic religious teaching and focuses on understanding Arabic texts. In this study, the research sample consisted of a group of students who took part in training using the Bahtsul Masa'il Method and another group of students who took part in conventional teaching methods. Data was collected through reading and comprehension tests of Arabic texts before and after implementing the method. The results of the test were analyzed using descriptive statistics and hypothesis testing to evaluate significant differences in improvement in reading ability between the two groups of students. The findings of this research indicate that the implementation of the Bahtsul Masa'il Method significantly increases the ability to read the Book of Fathul Qorib compared to conventional teaching methods. Students who underwent training with this method showed higher improvements in understanding Arabic texts. These results support the use of the Bahtsul Masa'il Method as an effective approach to improving reading competence in the context of Islamic religious studies. This research has positive implications for curriculum development and Islamic religious teaching methods, by emphasizing the importance of interactive approaches and critical thinking in understanding texts religion. In addition, this research provides an empirical basis for Islamic religious educators to consider using the Bahtsul Masa'il Method in an effort to increase understanding and literacy in Arabic among students.